Development of Entrepreneurship E-Module for Elementary School Students Based on Local Wisdom in Madura Island - Indah Setyo Wardhani; Rika Mellyaning Khoiriya (Universitas Negeri Malang, 2020)
The aim of this research is to develop a valid, practical and effective entrepreneurship e-module for Elementary School students in Madura. The validity level of the entrepreneurship e-module is known through the results of validation analysis by the validator. The level of practicality is known through observations of the use of entrepreneurship e-module, and the level of effectiveness known from two aspects, namely (1) the average score of students’ learning outcomes and (2) positive responses of the students. The development research model used to modify the 4D model by Thiagarajan and Sammel that consists of four stages, namely the stages of defining, designing, developing, and disseminating.